Accounting Profitability Analysis of Business Combination at PT Goto Gojek Toko Pedia, Tbk - M Fadlan Irfan Damanik; Aji Haviz; Azwan Bastian; Hasbiyana Haudi Nasution; Elisa Cici Prisilia; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the difference in profitability performance of PT Goto Indonesia Tbk before and after the business combination (PT Gojek Indonesia Tbk with PT Toko Pedia Tbk) in the period 2019-2022. This study uses secondary data taken from the Indonesia Stock Exchange (IDX) using a descriptive quantitative approach. Based on the results of the analysis, it shows that there is a difference in profitability ratios, namely ROA, ROE, NPM, and GPM between the period before the business combination in 2019-2020 and in the year after the merger, namely 2021-2022 with results showing an increase and decrease where in 2019 the ROA value was -1.13 then in 2020 it was -0.56 in 2021 it increased to -0.14 and in 2022 it decreased to -0.29. This shows that the company is still facing limitations in profitability, especially in the company's ability to generate profits from its total assets.